2015
DOI: 10.1647/2013-079
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Tear Production Using the Phenol Red Thread Test in the Common Mynah (Acridotheres tristis)

Abstract: To evaluate tear production in the common mynah ( Acridotheres tristis ) using the phenol red thread test (PRTT) and to make a comparison of measurements with the PRTT placed in the fornices of lower and upper eyelids, tear production of both eyes in 22 healthy adult captive mynah birds was evaluated. After positioning of threads in the fornices of upper and lower eyelids, the PRTT values of the birds were 17.5 ± 3.1 mm/15 s and 19.2 ± 2.5 mm/15 s, respectively. A significant difference was found between PRTT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
1
7
0
1
Order By: Relevance
“…Our mean results in the Livorno breed were similar to those of diurnal raptors (23.5 ± 8.9 mm/15 s) [34], while our mean results in the Siciliana breed were similar to those of large Psittaciformes (OD: 19.8 ± 4.3 mm/15 s; OS: 20.1 ± 3.9 mm/15 s) [35] and to those of the common mynah (19.2 ± 2.5 mm/15 s) [36].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our mean results in the Livorno breed were similar to those of diurnal raptors (23.5 ± 8.9 mm/15 s) [34], while our mean results in the Siciliana breed were similar to those of large Psittaciformes (OD: 19.8 ± 4.3 mm/15 s; OS: 20.1 ± 3.9 mm/15 s) [35] and to those of the common mynah (19.2 ± 2.5 mm/15 s) [36].…”
Section: Discussionsupporting
confidence: 85%
“…Given that there is an inter-specific difference in normal tear production in birds, reference values for each species need to be established (Table 5) [8][9][10][18][19][20][21][22][23]25,26,29,[34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Previously Barsotti and colleagues have shown tear production also in Eurasian Tawny owls, Little owls, Common buzzards, and European kestrels (Barsotti et al, 2013), however, we used the PRTT test instead of STT. A previous study has shown that after positioning of threads in the fornix of upper and lower eyelids, the PRTT values of the common Mynah birds were 17.5±3.1 mm/15 s and 19.2±2.5 mm/15s, respectively, showing a significant difference between PRTT values for upper eyelids and lower eyelids (Rajaei et al, 2015). In our study, we placed PRTT in the lower eyelid and results show 22.59±3.48mm/15s in the cygnet group and 22.5±3.63 mm/15s in all-bird group showing somewhat higher results than the current study.…”
Section: Methodsmentioning
confidence: 87%
“…A oftalmologia veterinária é uma área de grande importância para o manejo sanitário de animais silvestres e exóticos, devido a grande relevância ecológica e socioeconômica que vem aumentando pelo mercado lícito de animais e ao aumento dos cuidados médicos destinados a estas espécies, nos zoológicos e centros de triagem (Magalhães et al, 2004). Por se tratar em condutas médica diferente e diferentes diagnósticos, a oftalmologia em répteis se desenvolveu muito nos últimos tempos, com vários trabalhos sobre o estudo da anatomia e a fisiologia visual (Colitz et al, 2002;Delgado et al, 2014;Rajaei et al, 2015).…”
Section: Répteisunclassified